Helicobacter pylori Infection, Chronic Inflammation, and Genomic Transformations in Gastric MALT Lymphoma - Magdalena Witkowska; Piotr Smolewski (Hindawi Limited, 2013)
Nowadays, it is believed that the main role in the development of gastric mucosa-associated lymphoid tissue (MALT) lymphoma plays Helicobacter pylori infection. This world-wide distributed bacteria is in charge of most cases of not only upper gastrointestinal tract disorders but also some of extragastric problems. Constant stimulation of the immune system causes a B-lymphocytes proliferation, which is considered to be responsible for the neoplastic transformation. On the other hand, there are 10%-20% of patients who do not respond to Helicobacter pylori eradication treatment. This group has often a chromosome translocation, which suggests that there is another unknown, so far, pathogenetic mechanism of MALT lymphoma. Majority of genetic abnormalities are connected with nuclear factor-κB (NF-κB) pathway, which activates the uncontrolled proliferation of neoplastic cells. Translocations already described in studies are t(11;18)(q21;q21), which is the most common, t(14;18)(q32;q21), t(14;18)(q32;q21), and t(3;14)(p14.1;q32). This non-Hodgkin's lymphoma is an indolent type originated outside lymph nodes. In more than 50% of cases, it occurs in the stomach. Occasionally, it can be found in salivary and thyroid gland, lung, breast, bladder, skin, or any other place in the human body. This paper is a review of the current knowledge on etiology, pathogenesis, treatment, and follow-up of gastric MALT lymphoma.